A modified discrete filled function algorithm for solving nonlinear discrete optimization problems - Woon, Siew Fang; Rehbock, Volker; Loxton, Ryan (2012)
The discrete filled function method is a global optimization tool for searching for best solution amongst multiple local optima.This method has proven useful for solving large-scale discrete optimization problems.In this paper, we consider a standard discrete filled function algorithm in the literature and then propose a modification to increase its efficiency.